2013
DOI: 10.1016/j.cub.2013.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Mutation, Condition, and the Maintenance of Extended Lifespan in Drosophila

Abstract: The evolutionary theory of aging predicts that longevity will decline via drift or age-specific tradeoffs when selection favors early life fitness. Many Drosophila melanogaster populations continually terminated at young adult ages retain surprisingly long postselection lifespans. We compiled three decades of longevity data from the Ives population, demonstrating that postselective longevity was both substantial (30 days) and temporally stable over this period. Recently, alleles with positive pleiotropic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 50 publications
4
34
0
1
Order By: Relevance
“…First, positive mutational correlations are consistently found between different fitness components (62)(63)(64). Corresponding to this, the overall effects of deleterious mutations on any single component, as measured by the α andα parameters described above (Table S8), are often only a fraction of their net fitness effects (37,41,62,(65)(66)(67). Similarly, the net fitness reduction caused by homozygosity for second or third chromosomes extracted from natural populations is several times the corresponding reduction for viability (37,68).…”
Section: Quantitative Genetics Analyses Of Fitness Components In Drosmentioning
confidence: 99%
“…First, positive mutational correlations are consistently found between different fitness components (62)(63)(64). Corresponding to this, the overall effects of deleterious mutations on any single component, as measured by the α andα parameters described above (Table S8), are often only a fraction of their net fitness effects (37,41,62,(65)(66)(67). Similarly, the net fitness reduction caused by homozygosity for second or third chromosomes extracted from natural populations is several times the corresponding reduction for viability (37,68).…”
Section: Quantitative Genetics Analyses Of Fitness Components In Drosmentioning
confidence: 99%
“…R. Soc. B 281: 20141242 theoretical prediction has not been observed for flies maintained on this life cycle [45]. Note, however, that other studies in Drosophila have found that age-related effects on trait expression are largely trait-dependent; many traits do not exhibit a pronounced deterioration in function during the first two weeks of life, including metabolic rate, protein synthesis, geotaxis and fertility [60,61].…”
Section: Discussionmentioning
confidence: 83%
“…Two blocks were run approximately two weeks apart to allow for uncontrolled environmental effects. While our estimate of fitness only captured early-life fecundity, earlylife fitness appears to be genetically correlated with later-life fitness in D. melanogaster [36].…”
Section: (D) Fecundity Diallelmentioning
confidence: 99%